The impact of clusterization on the development of small and medium‐sized enterprise (SME) sector - Navickas, Valentinas; Malakauskaitė, Asta (Journal of Business Economics and Management, 2009)
The impact of clusterization on the development of SME sector has been analysed in this study. The cooperation of companies at national level and on a global scale is becoming more and more important as a tool of economic development. Companies tend to work together in order to share their competencies, reduce various costs, consolidate limited resources, and hereby increase their productivity, innovativeness, and profitability. It must be emphasized that the role of clusterization is crucial in the development of SME sector, as small and medium‐sized enterprises may benefit from economies of scale and extend the operation limits (size‐related limitations of operation are characteristic of most small businesses). Clusters (and similar forms of interorganizational structures) create the environment for innovation and technological advancement. Therefore, small and medium‐sized enterprises may gain additional benefits that include know‐how, cost‐saving options, innovative solutions, etc. The authors of this scientific study have concluded that the competitiveness of SME sector is closely related to the spread and extent of clusterization processes. First Publish Online: 14 Oct 2010